2001
DOI: 10.1046/j.0960-7412.2001.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, processing and export of cytoplasmic endo‐β‐1,4‐xylanase from barley aleurone during germination

Abstract: SummaryWe have identi®ed the major endo-b-1,4-xylanase (XYN-1) in the aleurone of germinating barley grain, and show that it is expressed as a precursor of M r 61 500 with both N-and C-terminal propeptides. XYN-1 is synthesized as an inactive enzyme in the cytoplasm, and only becomes active at a late stage of germination when the aleurone ceases to secrete hydrolases. A series of processing steps, mediated in part by aleurone cysteine endoproteases, yields a mature active enzyme of M r 34 000. Processing and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 42 publications
3
44
0
1
Order By: Relevance
“…4) that presumably directs secretion from cells in which they are synthesized. This is a significant observation, given recent indications that the (1 3 4)-␤-D-xylan endohydrolase involved in arabinoxylan depolymerization in germinated barley grain is not located in the endomembrane secretory compartment of aleurone layers but is found instead in the cytosol and is likely to be released from aleurone layers only after programmed cell death (56,57). In isolated aleurone layers, ␣-L-arabinofuranosidases and ␤-D-xylosidases are secreted and can be detected in the surrounding medium much earlier than the (1 3 4)-␤-xylan endohydrolases (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) that presumably directs secretion from cells in which they are synthesized. This is a significant observation, given recent indications that the (1 3 4)-␤-D-xylan endohydrolase involved in arabinoxylan depolymerization in germinated barley grain is not located in the endomembrane secretory compartment of aleurone layers but is found instead in the cytosol and is likely to be released from aleurone layers only after programmed cell death (56,57). In isolated aleurone layers, ␣-L-arabinofuranosidases and ␤-D-xylosidases are secreted and can be detected in the surrounding medium much earlier than the (1 3 4)-␤-xylan endohydrolases (10).…”
Section: Discussionmentioning
confidence: 99%
“…No biological rationale for COOH-terminal processing of the barley ARA-I and XYL enzymes can be provided at this stage. In the case of the barley (1 3 4)-␤-D-xylan endohydrolase, both NH 2 -and COOH-terminal processing of the primary translation product occurs (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…They are produced by a large variety of organisms including bacteria, fungi, and plants and are of significant importance in many physiological, pathological, and even biotechnological processes which involve degradation or remodeling of the plant cell wall. The physiological role of plant endogenous endoxylanases is linked to their involvement in processes such as secondary cell wall biogenesis and metabolism (1,36), germination (9,41), and the initiation of sexual reproduction by facilitating pollen tube penetration (35). Endoxylanases secreted by phytopathogenic microorganisms are generally considered (4) and occasionally proven (7) to be essential components of their offensive arsenal to penetrate and colonize plant tissues.…”
mentioning
confidence: 99%
“…DNA fragment markers are indicated on the right. rone layer, the processing produced many intermediates (16), and active enzymes of molecular masses of 55 and 30 kDa in wheat (27), and 29 (28), 34 (29), and 41 kDa (30) in barley have been reported. In addition, the tapetum xylanase is apparently encoded by a single gene in maize (15) and barley (this report), whereas the aleurone-layer xylanase is likely to be encoded by more than one gene (this report).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report (16) showed that during germination of barley seed, the aleurone layer contains a long xylanase-mRNA similar to that in the maize tapetum reported earlier (15). This barley mRNA produces a large precursor, which is processed to become an active xylanase of about 30 -34 kDa.…”
mentioning
confidence: 99%